Foreign-Owned Land - Eaton, Jonathan (American Economic Review, 1988)
While foreign investment augments the capital stock, it also affects land prices. If it causes land values to rise, then the resulting capital gain benefits current landowners, but the perma nent effect can be to reduce welfare. Other things equal, more-crowde d countries have higher land prices and lower steady-state welfare, b ut their net foreign indebtedness depends on technology, savings beha vior, and the interest rate. Even when it does not affect the domesti c capital stock, a land tax raises steady-state welfare. Copyright 1988 by American Economic Association.